Ethical Data Collection and Recognizing the Impact of Semi-Structured Interviews on Research Respondents - Husband, Gary (Education sciences, 2020)
This article explores the complex relationship between researcher and respondent through shared experience and interaction in the interview processes. Ethical considerations related to the balance of power and potential for change in respondents’ professional actions and decisions post-interview are discussed whilst problematizing the concept of truly informed consent. Informed by critical incident analysis, the article draws on the researcher’s experience of undertaking a qualitative-based study founded in the principles of phenomenological hermeneutics. Concluded in 2016, the research investigates the impact of pedagogical training programs on respondents’ teaching practice and engagement with professional learning. Respondents, experienced lecturers working in the adult education sectors in Scotland and Wales, contacted the researcher to share their post-interview experiences. The research was not designed to elicit change in respondents, nor influence professional choice or practice. However, each communication received attributed participating in the research as the source for renewed interest and engagement in professional learning. Although research interviews becoming an enriching experience for respondents is a recorded phenomenon the ascribed effects were profound, potentially life-changing, and not fully anticipated. Ethical considerations for researchers designing and undertaking interview-based research are considered alongside the potential for engagement in research interviews as a catalyst for professional learning in practice.